FETOMATERNAL OUTCOME AMONG PREGNANT WOMEN PRESENTED WITH OBSTETRIC CHOLESTASIS - REHMAN, N; ASLAM, S; SIDDIQUE, US; JAMIL, F; KHTTAB, AISA (Biological and Clinical Sciences Research Journal, 2024)
Obstetric cholestasis is a significant condition in pregnancy, associated with adverse fetomaternal outcomes, particularly at term. Timely diagnosis and management are crucial to mitigate complications. Objective: The aim of this study was to evaluate the fetomaternal outcomes among pregnant women diagnosed with obstetric cholestasis at term. Methods: This cross-sectional study was conducted from January 1, 2024, to July 1, 2024, in the Department of Obstetrics and Gynecology. Consecutive non-probability sampling was used to recruit women aged 18-40 years diagnosed with obstetric cholestasis at term. Patients with acute hepatitis, chronic kidney disease, or drug-induced hepatitis were excluded. Demographic data such as age, BMI, educational status, occupation, socioeconomic status, and residence area were recorded. Fetomaternal outcomes, including emergency cesarean section, sleep disturbances, postpartum hemorrhage, low birth weight (<2.5 kg), APGAR score <7, NICU admission, and meconium-stained liquor, were assessed. Results: A total of 120 patients were included in the study. The mean age of participants was 28.56 ± 6.40 years, and the majority were within the 18-30 years age group. Fetomaternal outcomes showed that 35% of the women required an emergency cesarean section. Sleep disturbances were observed in 54.2%, and postpartum hemorrhage occurred in 11.7% of cases. Low birth weight was recorded in 20.8% of neonates, while 10% had an APGAR score <7. NICU admission was required for 23.3% of the neonates, and meconium-stained liquor was present in 35.8% of deliveries. Conclusion: The study demonstrated significant fetomaternal outcomes in obstetric cholestasis, emphasizing the need for early detection and careful management to reduce complications such as higher rates of emergency cesarean sections, sleep disturbances, postpartum hemorrhage, low birth weight, and NICU admissions.